Integration of Field Data and Citizen Science in Spatial-Based Tropical Biodiversity Information Systems - Bustomi , Tommy; Adytia, Pitrasacha (STMIK Widya Cipta Dharma, 2025)
Biodiversity monitoring in tropical regions is often constrained by limited field survey coverage and fragmented data. This study develops a spatial information system that integrates field data collected through an Android application, citizen science contributions from iNaturalist, and environmental indicators such as the Normalized Difference Vegetation Index (NDVI) and land cover. The integration process employs a spatial database and ETL mechanisms for data normalization, quality validation, and spatial joins with raster data. The implementation results demonstrate that the system is capable of displaying biodiversity distribution in an integrated interactive map. Although citizen science data provide significant contributions, challenges remain in terms of data quality, participation bias, and the protection of sensitive species. With appropriate methodological approaches, this system has the potential to serve as a supporting tool for biodiversity monitoring and data-driven conservation planning.